Perancangan Ulang Struktur Atas Jembatan Gajah Wong Yogyakarta dengan Menggunakan Box Girder - Sentot Hardwiyono , Bagus Soebandono , Lukmanul Hakim (Universitas Muhammadiyah Yogyakarta, 2013)
The Gajah Wong bridge to be studied is located in road section of Selokan Mataram, connecting Gejayan Street and Seturan area, Sleman, Daerah Istimewa Yogyakarta Province. This bridge was built in order to increase economic and to support traffic activities in this area. Gajah Wong bridge has 40 m span. The designing of this bridge used I girder, and then would be done redesigning another form of prestressed-concrete bridge which is box girder. This redesign method being used is Bridge Management System (BMS) 1992. Excel is used to analyze the structure. AutoCAD 2010 software was utilized for scetching the design. Girder designed using prestressed concrete structures with cross-sectional profile of a trapezoid -shaped box girder type . In designing the structure beam is used full - prestress post-tensioning with trapezoidal cross section box with 2.5 m high with 0,3 m floor-slab thickness. Prestressed-steel using 7 strands which is based on ASTM A-416 specification and used angkur 28 pieces of VSL type E-55.